(3Mbhb GdeQCI hhGLHGJgG eJVefG TQMG dbGfhf GdCMhGd GdTNUjI ddeSdejf hGdMbhb GdeOfjI hGdSjGSjI ddeQCI (B((3habG ddePGgH GdNeSI haJGhi OGQ GdEaJGA GdeUQjI hdCMcGe eLdS GdOhdI hGdfbV hGdOSJhQjI GdYdjG(B) /s - (3fUjQ, CMeO eMeO eUWais ((3GdbGgQI (B:s (3OGQ GdfgVI GdYQHjI,s, 2011)
(3CKGQ ehVhY GdeQCI LOdG cHjQG Ydi UYjO GdegJejf HMbhb GdEfSGf, EP JHOh GdahGQb GdWHjYjI Hjf GdeQCI hGdQLd XGgQI, ceG Cf ecGfI GdeQCI aj GdfXe GdbGfhfjI GdSGHbI Ydi GdESdGe ZjQ eG gj Ydjg efP HYKI GdfHj eMeO Udi Gddg Ydjg hSde, MjK Maj GdESdGe HGdeQCI hCcQegG aLYdgG aj ecGfI dGFbI, aEPG HgG Jage OhQgG aj GdMjGI GdHTQjI adG JSeM HCf jfhH YfgG ZjQgG aj Jdc GdeSFhdjI hef gfG YfjJ GdfXe GdbGfhfjI GdeYGUQI HGdeQCI cPdc, hbO HOJ gPg GdYfGjI ajeG JVefJg GdehGKjb GdOhdjI hGdOSGJjQ GdeYGUQI ef CMcGe JgJe HTFhf GdeQCI aj cGaI eLGdGJ GdMjGI, HjO CffG bHd Cf fSJZQb aj JaGUjd gPG GdehVhY cGf dRGeG YdjfG ChdG Cf fHjf ddbGQF GdcQje deGPG fYbO GdebGQfI(B.s
(3HHdjhLQGajI (B: (3UaMI (B709-725.s
(3GdHMK aGFR HGdeQcR GdChd HGdeSGHbI GdbGfhfjI HQYGjI GdeLdS GdCYdi ddKbGaI dYGe (B2003s
Keywords: (3OGQ GdEaJGA GdeUQjIs; (3eUQ(B.s -- (3eLdS GdOhdIs; (3eUQ(B.s -- (3eMceI GdfbVs; (3eUQ(B.s -- (3GdeMceI GdYdjGs; (3GdeQCI (B((3abg ESdGej(B)s; (3GdESdGe hMbhb GdeQCIs; (3Mbhb GdeQCIs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdCMhGd GdTNUjI ddeSdejfs; (3GdMbhb GdeOfjIs; (3GdMbhb GdSjGSjIs; (3eLdS GdOhdIs; (3GdePGgH GdabgjIs